THE ROLE OF MIND MAPPING TO IMPROVE READING SKILL IN A2 LEARNERS - Ismatova Shakhnoza; Rajabova Laziza; Berdikulova Feruza (Western European Studies, 2024)
This study investigates how using mind mapping can improve reading abilities in A2 level students. Understanding the potential of mind mapping becomes crucial with the increasing significance of effective language acquisition strategies. This study seeks to clarify how mind mapping affects the understanding, memory, and involvement in reading activities for A2 learners by examining appropriate literature. The review includes different studies examining how mind mapping affects reading skills, offering a better understanding of the cognitive processes involved. Furthermore, it explores practical consequences for teachers and proposes possible directions for future research in this field. In general, the available literature emphasizes the potential of mind mapping as an effective tool for improving reading skills in A2 students.
Keywords: mind mapping; interference; reading competence; language proficiency